Discursos contrários e/ou avanços contidos: ensino médio politécnico, o estado e suas implicações no trabalho pedagógico - Corrêa, Marcos Britto (2017)
This dissertation is linked to Research Line 2: School Practices and Public Policies, from the Graduate Program in Education at Federal University of Santa Maria (UFSM) and Kairós - Group of Studies and Research on Work, Education and Public Policies. The main object of this study is the Curricular Restructuring of the High School of Rio Grande do Sul (Polytechnic Secondary School), which, in the scope of the State Department of Education (SEDUC-RS), changed the curriculum of the High School of Rio Grande do Su, between the years of 2011 And 2016. Through the dialectical analysis of the speeches of thirteen participants, being seven teachers and six students of a School in Santa Maria, as well as of documents on public educational policies, this study, subsidized by the theoretical-methodological contribution of the Historical Materialism Dialectic, aimed to answer the following question: With the senses of the participants of a school of the public education system, in their speeches, they describe how the State interferes in the production and implementation of a public educational policy? Thus, this dissertation did not analyze just how such policies affect school daily life, with its limits and possibilities, but also aimed to know how these policies are produced in the midst of its socio-historical conditions, which characterize Brazil as an economically dependent country. It is understood that analyzing the historicity of Brazilian State and its relation of economic dependence, in the sphere of international capitalism, contributed to know how educational public policies affect the pedagogical work of teachers in the school studied, a work understood as a fundamental category for the production of Knowledge in school. In addition, the pedagogical work category, in the dialectical analysis proposed in this research, helped to highlight the contradictions between public educational policies, the participants of the school and the way in which they are, in a critical process, active in school every day. Besides that, the analyzes made it possible to conclude that the limits of a policy such as Polytechnic Secondary Education are more effectively to the lack of time for its better implementation and, above all, the fragmentation resulting from changes in government. It is believed that these characteristics represent a structural process of the Brazilian State by its relation with capitalism in global scope, defining it as a dependent country, which reflects in the objectives, generally demanded by the capital, of public educational policies in order to impoverish its development. Specifically in the case of the Polytechnic High School, after seven years of its implementation, there is still little knowledge about the public policies that regulate it. However, the findings of this research show that, despite this short insertion period, there is active criticity of teachers and students in relation to the gaucho proposal.